2013
DOI: 10.1371/journal.pone.0072139
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Association between the CC Chemokine Ligand 5 (CCL5) -403 G>A Gene Polymorphism and Tuberculosis Susceptibility

Abstract: AimMany case-control studies have been performed in the recent past to investigate the association between CCL5 -403 G>A (rs2107538) gene polymorphism and tuberculosis (TB) susceptibility in various ethnic groups. However, these studies have produced inconsistent and contradictory results. In the present study, meta-analysis was performed to assess the association between CCL5 -403 G>A polymorphism and TB risk.MethodologyQuantitative synthesis was done for the published studies based upon association between C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Numerous studies have investigated the role of the CCL5 rs2107538 polymorphism in various diseases. Areeshi et al (29) performed a meta-analysis to evaluate the association between the polymorphism and tuberculosis susceptibility, and identified a significant link with increased risk of tuberculosis. In the study by Sáenz-López et al (11), the G/A + A/A genotype of CCL5 rs2107538 was reported to be significantly associated with an increased risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the role of the CCL5 rs2107538 polymorphism in various diseases. Areeshi et al (29) performed a meta-analysis to evaluate the association between the polymorphism and tuberculosis susceptibility, and identified a significant link with increased risk of tuberculosis. In the study by Sáenz-López et al (11), the G/A + A/A genotype of CCL5 rs2107538 was reported to be significantly associated with an increased risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sadek et al 31 reported that CCL5 levels on bronchoalveolar lavage fluid in patients with active PTB increased nearly 8 times higher than that in the control group. According to a previous study, 32 there is a significant association between the CCL5 -403 G>A polymorphism and increased risk of TB. Another study 33 showed that genetic polymorphism -28C>G in CCL5 is not associated with increased TB risk.…”
Section: Discussionmentioning
confidence: 86%
“…RANTES is a potent chemoattractant factor for monocytes and T cells and is associated with the function of cytotoxic T cells, which are important in the control of various intracellular pathogens (33). RANTES polymorphisms are associated with an increased risk of TB (34)(35)(36). In the current study, we found that recombinant RANTES protein or plasma RANTES did not signi cantly alter IL-1β production by macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%